Facilities and Infrastructure Management in Salaf and Modern Education: A Comparative Study of Islamic Boarding School Bahruttulab and Darussalam Banyuwangi - Rahmad Solihin; Purnomo, Joko (Universitas Islam Negeri Raden Intan Lampung, 2026)
Every educational institution has a distinct pattern of facilities and infrastructure management as a determinant of educational quality, as regulated in the National Education Standards; however, in practice, such management has not fully reflected optimal professionalism and standardization. This study aims to analyze and compare the management of facilities and infrastructure between traditional (salaf) and modern Islamic boarding schools based on the concepts of planning, organizing, implementation, and maintenance. Employing a qualitative approach with a comparative case study design, this research utilizes secondary data collected through observation, interviews, and documentation. Data analysis was conducted through data collection, reduction, display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal significant differences between islamic boarding school Bahruttulab and islamic boarding school Darussalam Banyuwangi, where the salaf pesantren tends to apply a flexible, needs-based management pattern, whereas the modern pesantren implements a more systematic and structured approach. Despite its contributions, this study has limitations; therefore, future research is recommended to involve a broader range of pesantren with diverse characteristics, apply quantitative or mixed methods approaches for more comprehensive findings, and develop an integrated facilities and infrastructure management model that combines pesantren values with modern management principles to systematically address the challenges of globalization in Islamic education.